Utilizando XML para publicação de dados multimídia na web - Teixeira, Eduardo Cotrin (2002)
Oriented-Object Database Management Systems have been adopted for the management of multimedia applications, becoming possible to implement recovery forms that propitiate more expression capacity to the user if are foreseen metadata (information about the stored data) that assist in this task, providing a more natural and powerful form to find objects in the objects base. In this context project AMMO (Authoring and Manipulation of Multimedia Objects) appeared, aiming to provide an environment for support the authoring, storage and manipulation of multimedia applications. The developed work aims to implement automatic XML document creation for representation of multimedia data obtained as result of consultations to the Multimedia Objects Server (MmOS) of AMMO environment, preserving the advantages of this environment, as possibility of content-based search, semantics description of multimedia data and high reusability, associating them with XML advantages, as interchange facility, independence and flexibility in presentation form and semantics description of content. The XML concepts, the AMMO Project, the XML representation of multimedia data with semantic information, the creation and use of XML documents inside AMMO Project and some possible forms of visualization of the data through the XSL Style Sheets are presented.